Manipulating raw noodle crystallinity to control the hardness of cooked noodle. (July 2019) - Tang, Aoxing; Li, Ming; Wang, Ruibin; Dhital, Sushil; Lu, Daxin
Abstract: An increase in the hardness during storage of Ready-to-eat (RTE)-cooked noodles is considered as a major quality problem. This study showed the noodle hardness can be manipulated by tuning the starch initial crystallinity with an explicit mechanism. Noodles were prepared from pre-gelatinized/native wheat starch and gluten with varied crystallinity from 12 to 17%. The noodle hardness at 4 °C for 21 days was monitored, which was significantly increased for all formulations from ca 51–183N during storage, accompanied by an increase in the retrogradation enthalpy and ordered structures studied using differential scanning calorimetry and Fourier transform mid-infrared spectroscopy respectively. Meanwhile, the crystallization rate of cooked noodles influenced the hardness of noodles with lower initial crystallinity, revealed from smaller k value and larger n value (Avrami equation). The starch initial crystallinity can also influence the starch retrogradation through varied inner structure during dough making. Highlights: Hardness of cooked noodles can be manipulated by tuning the initial crystallinity. Cooked noodles with lower initial crystallinity had smaller hardness along storage. Noodle hardness change in the early stage was due to fast amylose retrogradation. The retrogradation rate can influence the noodle hardness changing rate. Initial crystallinity affected the inner structure and influenced noodle hardness.